An Evaluation of Draminski Detector as an Early Detection Tool for Subclinical Mastitis in Dairy Cattle in Pondok Ranggon Farm - Pisestyani, Herwin; Permana, Indra; Basri, Chaerul; Lukman, Denny Widaya; Sudarwanto, Mirnawati (Jurnal Medik Veteriner, 2023)
Subclinical mastitis is one of the main problems in the development of dairy farming in Indonesia. Several screening test tools have been developed to support of control program for this problem. This study aimed to assess the suitability of the Draminski detector as a screening tool for subclinical mastitis in dairy cows. Quaternary milk samples from 27 dairy cows during normal lactation in the Pondok Ranggon area, East Jakarta were collected to be evaluated for the possibility of coming from quarters suffering from subclinical mastitis. Each milk sample was tested with 3 types of tests, i.e. the Breed method (golden standard) which was based on the number of somatic cells, the device Milkchecker which was based on electrical conductivity, and the Draminski detector which was based on electrical resistance. The results showed that the Draminski detector had a poor level of compatibility with the Breed method as the golden standard (Kappa value 0,013) and the Milkchecker tool (Kappa value 0,036). This test method was also considered to have poor test performance in diagnosing cases of subclinical mastitis in dairy cattle with a sensitivity value of 3,5%, specificity 100%, positive predictive value 100%, negative predictive value 18,8%, estimated prevalence 2,9%, and the true prevalence was 81,7%. In conclusion, the Draminski detector cannot be used to replace the Breed method and Milkchchecker as a screening test tool in cases of subclinical mastitis in dairy farms in Indonesia which were generally reared in the dairy farms.